Obat Nyamuk Bakar Berbahan Baku Limbah Batang Singkong Dan Ekstrak Biji Pala (Myritica fragans houtt) - Sandi Asmara; Winda Rahmawati; Sapto Kuncoro; Elhamida Elhamida; Muhamad Nurdin Yusuf; Yuyun Ari Trisnawati (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
In Lampung cassava stem waste is abundant, its existence is very disturbing, it is only thrown away and burned, it has not been utilized. Its use as an insect repellent is one of the value-added treatment efforts. The purpose of this study was to study the effect of tapioca glue adhesive concentration on the characteristics of mosquito coils at several concentrations of cassava stem powder and nutmeg powder. The treatment, the concentrations of cassava stem powder, nutmeg powder, and tapioca glue adhesive were; a) 16.67%, 26.04%, 58.34%, b) 16%, 24%, 60%, c) 15.38%, 23.07%, 61.53%, d) 14.81 %, 22.23%, 62.9%, and e) 14.28%, 22.32%, 64.28%. This research was conducted to study the physical characteristics (moisture content, density, shatter resistance index, combustion rate, smoke distribution, and organoleptic tests). The method used in this study was a completely randomized design measured using the Indonesian Industrial Standard (SII) No. 1113-84. The results showed that the variety of treatments with the addition of tapioca adhesive in the manufacture of mosquito coils had a very significant effect on moisture content, density, shatter resistance index, and burning time.Â